Newly Emerging Pest in China, Rhynchaenus maculosus (Coleoptera: Curculionidae): Morphology and Molecular Identification with DNA Barcoding - Yang, Rui-Sheng (Insects, 2021)
SIMPLE SUMMARY: Accurate and rapid species identification is crucial in early monitoring and intervention of a pest, especially for a new and emerging pest. Here, the first detailed morphological features of Rhynchaenus maculosus at four life-cycle stages are reported for traditional species identification. Morphology-based identification is not only time-consuming but often inconclusive for closely related sibling species, juveniles, and even not feasible in the absence of key morphological characters. To overcome the limitations of traditional methods in species identification, DNA barcodes (mitochondrial cytochrome C oxidase subunit 1, CO1) were successfully used to identify the pupal and larval specimens as R. maculosus and allocate the undetermined morphospecies in GenBank into their possible taxa. The integration of molecular identification with the morphology-based identification proved to be effective in the accurate and rapid identification of R. maculosus. ABSTRACT: The oak flea weevil, Rhynchaenus maculosus Yang et Zhang 1991, is a newly emerging pest that severely damages oak (genus Quercus) in China. The first R. maculosus outbreak occurred in 2020 and caused spectacular damage to all oak forests in Jilin province, northeast China. The lack of key morphological characters complicates the identification of this native pest, especially in larva and pupa stages. This is problematic because quick and accurate species identification is crucial for early monitoring and intervention during outbreaks. Here, we provided the first detailed morphological description of R. maculosus at four life stages. Additionally, we used DNA barcodes from larva and pupa specimens collected from three remote locations for molecular identification. The average pairwise divergence of all sequences in this study was 0.51%, well below the 2% to 3% (K-2-parameter) threshold set for one species. All sample sequences matched the R. maculosus morphospecies (KX657706.1 and KX657707.1), with 99.23% to 100% (sequence identity, E value: 0.00) matching success. The tree based on barcodes placed the specimens into the Rhynchaenus group, and the phylogenetic relationship between 62 sequences (30 samples and 32 from GeneBank) had high congruence with the morphospecies taxa. The traditional DNA barcodes were successfully transformed into quick response codes with larger coding capacity for information storage. The results showed that DNA barcoding is reliable for R. maculosus identification. The integration of molecular and morphology-based methods contributes to accurate species identification of this newly emerging oak pest.